Irregularly Sampled Time Series Interpolation for Detailed Binary Evolution Simulations - Philipp M. Srivastava; Ugur Demir; Aggelos Katsaggelos; Vicky Kalogera; Shamal Lalvani; Elizabeth Teng; Tassos Fragos; Jeff J. Andrews; Simone S. Bavera; Max Briel; Seth Gossage; Konstantinos Kovlakas; et al. (The Astrophysical Journal)
Modeling of large populations of binary stellar systems is an integral part of many areas of astrophysics, from radio pulsars and supernovae to X-ray binaries, gamma-ray bursts, and gravitational-wave mergers. Binary population synthesis codes that employ self-consistently the most advanced physics treatment available for stellar interiors and their evolution and are at the same time computationally tractable have started to emerge only recently. One element that is still missing from these codes is the ability to generate the complete time evolution of binaries with arbitrary initial conditions using precomputed three-dimensional grids of binary sequences. Here, we present a highly interpretable method, from binary evolution track interpolation. Our method implements simulation generation from irregularly sampled time series. Our results indicate that this method is appropriate for applications within binary population synthesis and computational astrophysics with time-dependent simulations in general. Furthermore, we point out and offer solutions to the difficulty surrounding evaluating the performance of signals exhibiting extreme morphologies akin to discontinuities.